Aspects of the Innovation Activities of Small and Medium Business - Melnikas, Borisas; Jakubavičius, Artūras (Ekonomika, 1999)
In this article are discussed the important problems of economic and innovation in a small and medium business. Is summarised the main regularity in a small and medium business and are presented possibilities for the further development of an innovation activity. The innovation activity is presented as a system. Is presented methodology of innovation appraisal. Is made a summary of the research concerning economic processes in the sphere of innovation activity. Are made recommendations on the development of organisation management models, which are helpful in efficient organisation of an innovation activity.